MANAJEMEN KINERJA DALAM MENDUKUNG EFEKTIVITAS PEMERINTAHAN DAERAH (Studi pada Sistem Akuntabilitas Kinerja Pemerintah di Kabupaten Tana Tidung): (Studi pada Sistem Akuntabilitas Kinerja Pemerintah di Kabupaten Tana Tidung) - Astuti, Deviyanti (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Abstract: Performance Management in Supporting Regional Government Effectiveness (Study of Performance Accountability Systems in Tana Tidung Regency). The Government Agency Performance Accountability System (SAKIP) of Tana Tidung Regency 2023 received a B designation from the Ministry of Administrative and Bureaucratic Reform. However, the measurement of efficiency in the use of budget effectiveness, which has a direct impact on the community, has not been felt by the community, as shown by the poverty rate, which continues to rise. The research revealed the inhibiting and supporting factors for implementing SAKIP in the Tana Tidung Regency Government. Inhibiting factors include 1) information technology by implementing computerized performance monitoring or computerized performance management (CPM) control; 2) rewards and punishment do not consider ASN performance; 3) inappropriate organizational structure (rightsizing). Apart from that, there are supporting factors for the performance of SAKIP implementation, including: 1) work culture (Core Value) with commitment from the regional government and central government influencing performance accountability supported by commitment between agencies in controlling the implementation of performance measurement for the Tana Tidung Regency government, 2) quality and quantity of sources apparatus power. This can be taken into consideration in performance planning, measuring, and managing performance data, and performance evaluation reviews to increase the effectiveness of impactful government performance management.